Case Study in Evaluation and Performance of Metallic and Polymer Coating as Corrosion Protection In Marine Environment - Kamdi, Zakiah; Mohd Faruq (Research Progress in Mechanical and Manufacturing Engineering, 2020)
Marine corrosion damaged will cause loss of huge cost to the industries. As a preventive method, the coating of a substrate is required to sustain the damaged due to corrosion damaged. The marine corrosion will affect the industries such as oil and gas industries and maritime industries. Therefore, this study is relating to the evaluation of the metallic coating and paint coating performance as corrosion protection in the marine environment. The numerical study had been carried out by using different parameter and type of coating. Each coating has its own method and technique used for applying the coating to metal. For examples, the metallic coating can be applied via electroplating, hot-dip galvanizing and thermal spray and for polymer or paint coating can be applied via brushing or air compressed spray. However, the main focus of this researched is a concern about how it performs under corrosion test in the marine environment such as the immersion test and salt spray test. The corrosion behavior of the coating can be measured via electrochemical impedance spectroscopy (EIS) test. The x-ray diffraction (XRD) and scanning electron microscope (SEM) were used to analyze the phases and microstructure of the coating.